Neonatal Sepsis and Its Associated Risk Factors : A Case Control Study in Tertiary Care Hospital in Chattogram (Journal of Chittagong Medical College Teachers' Association, 2025)
Background: Neonatal sepsis is a clinical syndrome resulting from the pathophysiologic effects of local or systemic infection. It is one of the major cause of morbidity and mortality of neonate and is an enduring major global public health challenge predominantly in developing countries. The objective of this study is to evaluate the risk factors association with neonatal sepsis in tertiary care hospital of Chattagram Maa Shishu O General Hospital (CMSOGH), Chattogram.Materials and methods: The study was a prospective type of case control study, conducted from October to December 2023, in the tertiary care hospital of Chattogram. A total sample 150 were selected, among them 50 cases, were proven sepsis through clinical and laboratory criteria of IMNCI (Integrated Management of Neonatal and Childhood Illness were incorporated as cases in this study. Those were neither suspected nor diagnosed sepsis but admitted to the Neonatal Ward of CMSOGH due to other indications such as low birth weight, neonatal jaundice, diarrhea etc. throughout the study period were included as controls. The chi square test was used to test the association between dependent and independent variables associated with risk factors to neonatal sepsis.Results:  Late onset neonatal sepsis was common among neonatal sepsis and maternal age